(untitled) (Al-Aasar, 2025)
District Bajaur holds a distinguished position in the field of Islamic scholarship, where eminent scholars rendered valuable services in Qur’anic exegesis. This study presents an analytical review of their exegetical contributions, reflecting both traditional and modern approaches to the Tafseer. We will discuss about some prominent scholars and analyse their methodologies in the explanation of the chapters of holy Quran. Like Maulana Muhammad Sharif dedicated his teaching sessions to promoting Qur’anic understanding and strengthening the spiritual bond with the Holy Book. Similarly, Maulana Qazi Abdul Ghafoor’s audio Tafseer is remarkable for its eloquence and accessibility, addressing contemporary socio-religious challenges. Maulana Khurshid Ahmad and Maulana Muhammad Yar Badshah contributed through public lectures and educational efforts, while Maulana Muhammad Sadiq highlighted the Qur’an as a comprehensive code of life. Among written works, Fath al-Rahman by Sheikh Abdul Jabbar stands out as a methodical Tafseer, combining logical reasoning with literary refinement, whereas ‘Aqd al-Juman by Senator Maulana Abdul Rashid reflects a unique scholarly approach that integrates jurisprudential, theological, and exegetical dimensions. Moreover, the audio Tafseer of Maulana Abdul Rahim played a pivotal role in conveying the Qur’an’s message to the grassroots level, while the Tafseer of Sheikh Inayatullah Bajauri, known for its simplicity and wisdom, deeply influenced the masses.The findings reveal that Bajaur’s scholars not only preserved the intellectual and spiritual bond with the Qur’an but also provided solutions for contemporary needs through diverse exegetical methods. Their legacy remains a significant contribution to Islamic thought and a source of inspiration for future generations.